2019
DOI: 10.3390/md17050283
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Characterization of Two New Metabolites from the Sponge-Derived Fungus Aspergillus sp. LS34 by OSMAC Approach

Abstract: The application of an OSMAC (One Strain-Many Compounds) approach on the sponge-derived fungus Aspergillus sp. LS34, using two different media including solid rice medium and potato dextrose broth (PDB) resulted in the isolation and identification of two new compounds, named asperspin A (1) and asperther A (2) along with seven known compounds 3–9. Compounds 1–5 were detected in fungal extracts from rice medium, while compounds 6–9 were isolated from PDB medium. Their structures were unambiguously characterized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 27 publications
0
13
0
1
Order By: Relevance
“…Natural product Altered conditions [17] Additives such as solvents, heavy metals, tensides, precursors, and other small molecule elicitors are also useful for the elicitation of secondary metabolite production in microorganisms. Chen reports that organic solvents can either increase (DMSO, EtOH) or decrease (THF, DMF) the production of antibiotics such as tetracenomycin and thiostrepton in Streptomyces strains [18].…”
Section: Strainmentioning
confidence: 99%
“…Natural product Altered conditions [17] Additives such as solvents, heavy metals, tensides, precursors, and other small molecule elicitors are also useful for the elicitation of secondary metabolite production in microorganisms. Chen reports that organic solvents can either increase (DMSO, EtOH) or decrease (THF, DMF) the production of antibiotics such as tetracenomycin and thiostrepton in Streptomyces strains [18].…”
Section: Strainmentioning
confidence: 99%
“…The in vitro cytotoxic activities of all isolated compounds against four human cancer cell lines (CCRF-CEM, MDA-MB-231, HCT-116, and AGS) were evaluated by the MTT method as previously described (Huang et al, 2019;Li W. et al, 2019). 7-Ethyl-10hydroxycamptothecin (1.3, 10.8, 9.9, and 4.2 nM, respectively) was used as the positive control against four above-mentioned human cancer cell lines.…”
Section: In Vitro Cancer Cell Cytotoxicity Assaysmentioning
confidence: 99%
“…As part of a continuing research program investigating the biologically active secondary metabolites from sponge-derived fungi (Ding et al, 2018;Huang et al, 2019;Li W. et al, 2019), a detailed chemical investigation was initiated on the culture of fungus Aspergillus sp. NBUF87.…”
Section: Introductionmentioning
confidence: 99%
“…Among these, algae-derived fungi have been reported to be the largest source of secondary metabolites with diversified bioactivities [1,2], and that can be exploited potentially as lead compounds for new drug development. It was reported that by employing one of the post-genomic strategies, one strain many compounds (OSMAC), on the cultivation of the fungal strains could enhance the quantity and diversity of fungal secondary metabolites [3,4]. The OSMAC approach usually involved the manipulation of culturing parameters, such as media formulation, temperature, agitation, luminosity, aeration, etc.…”
Section: Introductionmentioning
confidence: 99%
“…enhance the quantity and diversity of fungal secondary metabolites [3,4]. The OSMAC approach usually involved the manipulation of culturing parameters, such as media formulation, temperature, agitation, luminosity, aeration, etc.…”
Section: Introductionmentioning
confidence: 99%